2007
DOI: 10.1007/978-3-540-75757-3_71
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Trajectory Planning for Deep Brain Stimulation: A Feasibility Study

Abstract: Abstract. DBS for Parkinson's disease involves an extensive planning to find a suitable electrode implantation path to the selected target. We have investigated the feasibility of improving the conventional planning with an automatic calculation of possible paths in 3D. This requires the segmentation of anatomical structures. Subsequently, the paths are calculated and visualized. After selection of a suitable path, the settings for the stereotactic frame are determined. A qualitative evaluation has shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 12 publications
0
44
0
Order By: Relevance
“…The entry point is varied while, for each trajectory, a cost function is evaluated and the system operator selects the best trajectory. Bruneberg et al facilitated a segmentation of the STN and determined the optimal trajectory by avoiding ventricles, gyri, and blood vessels, which need to be segmented beforehand [5]. Khlebnikov et al suggested a system to find optimal access paths by interpreting tumors as light sources and determining the cost-function based on light transport [15].…”
Section: Related Workmentioning
confidence: 99%
“…The entry point is varied while, for each trajectory, a cost function is evaluated and the system operator selects the best trajectory. Bruneberg et al facilitated a segmentation of the STN and determined the optimal trajectory by avoiding ventricles, gyri, and blood vessels, which need to be segmented beforehand [5]. Khlebnikov et al suggested a system to find optimal access paths by interpreting tumors as light sources and determining the cost-function based on light transport [15].…”
Section: Related Workmentioning
confidence: 99%
“…In other related work [6,[8][9][10], trajectory optimization is based on a pre-calculated distance map that encodes the minimal distance of a voxel from a critical structure. This method is computationally efficient because the distance map is computed only once and applied to every trajectory.…”
Section: Automatic Trajectory Planningmentioning
confidence: 99%
“…The weights are chosen by the neurosurgeons to represent the relative importance of each constraint. A greater weight is usually given to the risk max criterion because almost hitting a critical structure once is more severe than approaching the same critical structure multiple times at a safer distance [8]. On the other hand, the sum criterion is useful because it distinguishes among cases where a trajectory approaches a critical structure once or multiple times along the path [9].…”
Section: Automatic Trajectory Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…A common practice is manual selection and assessment of the suitability of different entrance positions on the scalp surface of the patient in order to select an appropriate insertion path. To process, visualize and manipulate large volumes of 3D imaging datasets, automated surgical planning methods have been proposed in recent years [1], [2], [3], [4], [5], [6]. The current trend is to move as much of the planning tasks as possible into the operating room to avoid errors that can appear because of the discrepancies between pre-operative images and intra-operative images.…”
Section: Introductionmentioning
confidence: 99%